O olhar de adolescentes-alunos/as sobre o sentido da vida : interações com um contexto escolar - Alves, Silvia Cristina Hack (2009)
The search for the meaning of life is closely related to human condition. In many ways, people are looking for meaning to their existence and this happens especially when faced with limitations, the fact of being mortal and realize their own imperfections. Arise in adolescence, more intense, the questions related to the reason of existence. The search for the meaning of life becomes a constant in the lives of most the teenagers who, in turn, are faced with the need to make key choices that will guide the course of your life. This research is devoted therefore to provide a current view of adolescents-students as belonging to a public school in the city of Canoas-RS indicate the direction of his life and whether these concepts are included or not in the school where developed the research. The relevance of this research is therefore in fact know how students / teenagers to interpret the meaning of their existence now and see if important elements of life the teenagers are being considered in the school, allowing closer approximation of the universe juvenile with the field school. We know, however, that several factors are present and influence the mode of living the teenagers, among them the strong presence of culture. The adolescents become the products of the current culture, but also produce new forms of cultural expression and practices. It is through culture that the youth / adolescent to often find ways to adopt a lifestyle for you. According to data obtained through this search, you can also see that issues such as relationships and the question of obtaining a good job are related to the meaning of life the teenagers surveyed. The faith and way of conceiving God items are also present at the stage of adolescence. The adolescence leads to the school and experience in many of the issues related to his life and sees the school not only as a space where developing the teachinglearning process, but also as a place to exercise their sociability. The current public school, however, faces difficulties and is going through crisis, and often can not establish the necessary links between the interests and issues of existential a student with their own issues. Thus, several times, the real anxieties, desires and the experiences the adolescent and the needs and specificities from adolescence, are not considered by the school environment, is emerging and intensifying tensions and conflicts between adolescents and school.